Analisis Terhadap Fenomena Jilbab di Indonesia: Studi Surah Al Ahzab Ayat 59 dan An Nur Ayat 31 - Kartin Potutu (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to analyze the Hijab phenomenon in Indonesia. By examining the Contextualization of QS.AL-Ahzab: 59 and QS. An-Nur:31 with the current phenomenon, reviewing the history of the veil before Islam, the hijab in the time of the Prophet until now the hijab culture in Indonesia has become a trend fashion that can generate rupiah for clothing entrepreneurs. The analytical method used in this research is descriptive analysis with a qualitative approach. This research reviews the history of the headscarf before Islam came, the time of the Prophet and his companions, the history of the headscarf entered Indonesia until now the headscarf has become very phenomenal in Indonesia. The results of the study show that women wearing headscarves in Indonesia have been increasing lately. Some decided to wear the headscarf after going through a long struggle and finally believed that it was the dress that Islam required. Some wear the headscarf because they are forced by the rules, especially because there are many regional regulations regarding the obligation to wear the headscarf. Partly for psychological reasons, she doesn't feel comfortable because everyone in her neighborhood wears the headscarf. There are more for fashionable reasons, to make it look more beautiful and trendy, as a response to the challenges of the modeling world which is very familiar with women. There are also those who wear headscarves because they sell headscarves. There are even those who wear headscarves for political reasons, namely to fulfill the demands of certain Islamic groups who tend to prioritize religious symbols as political merchandise. Currently Hijab has experienced a shift in value.